Promising Anthelmintic Properties of Papaya (Carica Papaya) Extract: A Literature Study - An-Nisa, Syanur; Putri, Silma Amalia; Affandi, M Luqman; Pawestri, Aulia Rahmi (Fakultas Kedokteran Universitas Brawijaya, 2024)
Helminthiasis is a lurking health issue worldwide. Currently, available anthelmintics focus on the benzimidazole group, despite their side effects and threats of anthelmintic resistance. Therefore, exploration of novel compounds with anthelmintic properties is crucial. Papaya (Carica papaya) contains active compounds with prospective anthelmintic properties. This literature review discusses the potential of papaya as an anthelmintic agent. We screened publications from indexed journals in English and Indonesian published between 2013–2023 covering topics of C. papaya active compounds and their anthelmintic properties. Seeds, leaves, bark, and stems of papaya showed various degrees of anthelmintic properties. Studies reported its efficacy against several helminth species with good safety profiles. C. papaya extract can be a promising anthelmintic candidate. Aside from its abundance, its effectiveness and safety yielded satisfactory results. Further research is needed to elicit the mechanism of C. papaya as a novel therapeutic modality for parasitic infections.